Caudatan A, an undescribed human kidney-type glutaminase inhibitor with tetracyclic flavan from Ohwia caudata. (August 2018) - Sun, Yiwei; Feng, Xiaohe; Liu, Xuanli; Qian, Cheng; Che, Xin; Cao, Fei; Jin, Sanshan; Meng, Dali
Abstract: Human kidney-type glutaminase (KGA) is an important target that is often over expressed in many cancer cells but very few effective inhibitors of this enzyme have yet reached clinical trials. Caudatan A and caudatan B, two undescribed tetracyclic flavans with an unusual ether bond between the C-4 and C-2′ were isolated from the roots of Ohwia caudata (Thunb.) H.Ohashi. Caudatan A exhibited stronger inhibitory activity and caudatan B showed moderate effect from the results of inhibitory activities evaluations on KGA. The molecular docking and primary structure-activity relationship analysis revealed that the less steric hindrance at ring A was necessary to the effect. Therefore, combined its better solubility than that of bis-2-(5-phenylacetimido-1, 2, 4-thiadiazol-2-yl)ethyl sulfide (BPTES), caudatan A might be the potential candidate as the inhibitor of KGA for further studies. Graphical abstract: Two undescribed tetracyclic flavan skeleton compounds were extracted from the roots of O. caudatum. One of them, caudatan A, could occupy the major active site of KGA and exhibited stronger inhibitory activities. Image 1 Highlights: Two undescribed tetracyclic flavans were isolated from the roots of Ohwia caudate. The absolute configurations were determined. Two novel tetracyclic flavans exhibited significant inhibitory activities on KGA. Caudatan A could binding to the active site of KGA steady in molecular docking.